Everything she didn't say - Kirkpatrick, Jane, 1946- (Revell, a division of Baker Publishing Group, 2018)
In 1911, Carrie Strahorn wrote a memoir entitled Fifteen Thousand Miles by Stage, which shared some of the most exciting events of 25 years of traveling and shaping the American West with her husband, Robert Strahorn, a railroad promoter, investor, and writer. That is all fact. Everything She Didn't Say imagines Carrie nearly ten years later as she decides to write down what was really on her mind during those adventurous nomadic years. Certain that her husband will not read it, and in fact that it will only be found after her death, Carrie is finally willing to explore the lessons she learned along the way, including the danger a woman faces of losing herself within a relationship with a strong-willed man and the courage it takes to accept her own God-given worth apart from him. Carrie discovers that wealth doesn't insulate a soul from pain and disappointment, family is essential, pioneering is a challenge, and western landscapes are both demanding and nourishing. Most of all, she discovers that home can be found, even in a rootless life.